Dynamics of illegal wildlife trade in Indonesian markets over two decades, illustrated by trade in Sunda Leopard Cats. Issue 1 (2nd January 2019) - Nijman, Vincent; Ardiansyah, Ahmad; Bergin, Daniel; Birot, Hélène; Brown, Ella; Langgeng, Abdullah; Morcatty, Thais; Spaan, Denise; Siriwat, Penthai; Imron, Muhammad Ali; Nekaris, K. Anne-Isola
ABSTRACT: Wildlife trade is recognised as an impediment to conservation. Yet, long-term trade data are lacking for many species, precluding analysis of trends and trade dynamics. The Sunda Leopard Cat is endemic to insular Southeast Asia, where despite legal protection, it is openly traded. Data from Java and Bali (1996–2018, 393 surveys, 219 cats recorded in 21 markets) reveal that numbers of cats decreased (1.95/survey in the 1990s, 0.44/survey in the 2010s) and their prevalence decreased (from 46% to 30% of surveys recording cats). Invariably in the animal markets other protected wildlife was for sale, even if Sunda Leopard Cats were not present. Corrected for inflation, prices were higher in recent years (US59 vs US26) and higher in markets with low availability, possibly indicating an Anthropogenic Allee Effect whereby a premium is paid for rare species. Direct comparisons between markets reveal a complicated pattern with evidence of a significant decrease from only one market, but clear shifts of the trade between markets. Despite legal protection, we conclude that leopard cats are still commonly traded in Java, alongside other protected wildlife, albeit in smaller numbers than before.